A First Report of Secondary Hemophagocytic Lymphohistiocytosis Associated With Papillary Thyroid Carcinoma. Issue 2 (March 2018) - Wakefield, Connor; Mehta, Parinda A.; Corathers, Sarah; Geller, James; Gelfand, Michael; Olowokure, Olugbenga; Marsh, Rebecca A.
Abstract : Secondary hemophagocytic lymphohistiocytosis (HLH) is a rare and potentially fatal immune-deficiency disorder that develops in response to diseases that produce strong immunologic activation, such as infection and malignancy. Although secondary HLH is reported to occur in association with various malignancies, there is no report of its association with thyroid cancer. We evaluated a 19-year-old man who presented with HLH. During investigation for an underlying cause of his HLH computed tomographic scan of the neck discovered thyroid nodules that were confirmed with biopsy to be papillary thyroid carcinoma. He was treated with surgery followed by radioactive iodine therapy and remains without any recurrence of malignancy or his secondary HLH. This report documents the first observation of HLH associated with thyroid cancer, and illustrates the need to include imaging of the neck while evaluating patients with secondary HLH for an underlying malignancy.